Early-life famine exposure increases the risk of subsequent physical disability: evidence from a national population-based survey - Shiwei Cao; Yao Wu; Tengfei Niu; Xiyu Chen; Jie Xiang; Hao Li; Ziyi Chen; Qianying Shi; Yu Du; Yu Du (Frontiers in Public Health)
BackgroundDue to ethical constraints, famines, which can lead to severe malnutrition, are often viewed as natural experiments to assess the impact of early-life nutritional malnutrition on adverse health outcomes in adulthood. However, evidence regarding the effect of early-life famine exposure on later-life physical disability remains scarce. This study aims to investigate the association between early-life famine exposure and physical disability in the Chinese population.MethodsThis study is based on survey data from the China Health and Retirement Longitudinal Study released in 2018. Famine exposure was determined based on participants’ birth years, and all individuals were categorized into four groups: non-exposed, fetal exposed, preschool exposed, and school-age exposed. Logistic regression analysis was conducted to examine the association between early-life famine exposure and physical disability. Stratified analyses were further performed by gender, residence, and severity of early-life famine exposure.ResultsAfter adjusting for all covariates, fetal exposure to famine was associated with a 1.57-fold increased risk of severe disability compared to the non-exposed group. Among males, older people with fetal exposure to famine was significantly associated with a 1.69-fold increased risk of severe disability compared to the non-exposed group. Among females, older populations with famine exposure during the school-age period was associated with a 1.52-fold increased risk of severe disability compared to the non-exposed group. In areas with less severe famine exposure, those with fetal exposure was linked to a 1.66-fold increased risk of severe disability compared to the non-exposed group. In areas with more severe famine exposure, older individuals exposed during the preschool period had a 1.57-fold higher risk of mild disability. In rural areas, older adults who were exposed to famine during the fetal period had a 1.65-fold increased risk of severe disability compared to their non-exposed counterparts. In urban areas, those exposed to famine during the preschool period exhibited a 1.63-fold higher risk of mild disability than their non-exposed counterparts.ConclusionThe findings underscore the critical role of early-life adversity and nutritional status in shaping health outcomes in later life, highlighting the need for public health policies to prioritize nutritional interventions during early developmental stages.